(untitled) (International Journal of Food and Nutritional Sciences, 2022)
.The modern agriculture has increased the use of inputs especially for seed, fertilizers, irrigational water, machineries and implements, which has increased demand for agricultural credit. The adoption of modern technology, which is capital intensive, has commercialized agricultural production in India. Besides, the farmers‟ income is seasonal while his working expenses are spread over time. In addition, farmer’sinadequate savings require the uses of more credit to meet the increasing capital requirements. Furthermore, credit is a unique resource, since it provides the opportunity to use additional inputs and capital items now and to pay for them from future earnings. In this context, this study is an attempt to find out the farmers’ perception towards agricultural finance provided by SBI in Sedam taluka, Kalaburagi district of Karnataka.